Does the shared vision of social identities influence the quality of civil construction by reinforcing the type of thermal insulation, and by creating or improving thermal comfort? - Ziad, Slimane; Benoudjafer, Imane; Benoudjafer, Ibtissame (Technium Social Sciences Journal, 2023)
The building sector in Algeria is one of the most energy intensive sectors due to the lack of culture of thermal insulation among the occupants and the lack of awareness in the use of this technique to obtain better thermal comfort in the long term and reduce energy bills. This article aims to study the influence of the shared vision of social identities on the quality of existing civil constructions by reinforcing the type of thermal insulation to achieve better thermal comfort for individuals regardless of the conditions climatic. To do this, we first presented a general description of the current context of construction and the available materials used in the city of Bechar. Then a general analysis on the different techniques induced in the construction of the envelope (exterior walls and roofs) in order to select the best technique that adapts to the climate of Bechar (hot and arid) and strengthening it to improve the thermal comfort of residential homes with lower energy consumption.